2022
DOI: 10.1007/s10853-021-06244-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of iron-based magnetic nanoparticles stabilized with triethanolammonium oleate for theranostics

Abstract: The novel iron-oxide nanoparticles (NPs) stabilized with triethanolammonium oleate were produced. The specimens were divided into two groups: the top NPs (extracted from the supernatant) and the bottom NPs (nanoparticles sedimented at the bottom of the flask during centrifugation), respectively. The XRD and Mössbauer studies revealed a presence of the Fe3O4 phase in both types of nanoparticles. Furthermore, the formation of maghemite layer on the surface of nanoparticles was observed. Average particle sizes de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…This means that the heating rates would be different at the bottom and the center of the vial. Indeed, a previous work has shown that the time needed to reach the hyperthermia limit on the bottom is 8 times faster than that of the top of the vial …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that the heating rates would be different at the bottom and the center of the vial. Indeed, a previous work has shown that the time needed to reach the hyperthermia limit on the bottom is 8 times faster than that of the top of the vial …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a previous work has shown that the time needed to reach the hyperthermia limit on the bottom is 8 times faster than that of the top of the vial. 63 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferrites transition elements are promising candidates for medical applications due to a successful combination of their technical parameters: ease of synthesis and presence of magnetic properties. Iron oxide compounds exhibit antibacterial properties and are nontoxic [ 8 ], which allows them to be considered as promising materials for theranostics [ 9 , 10 ]. The nanoparticles’ developed surface displays an increased adsorption activity [ 11 ], which can be used for organic–inorganic composite materials synthesis [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-modal treatments have become routine in cancer treatments to maximize the therapeutic killing of cancer cells, while minimizing the impact of side effects. The material described in this paper brings a second therapeutic in the form of magnetic nanoparticles that can be heated by an alternating magnetic field to locally heat and kill cancer cells in a treatment called hyperthermia [3]. In this material, though, there is also a thermally responsive polymer, poly(N-isopropylacrylamide), that has been shown to induce drug release when heated above its transition temperature [4].…”
mentioning
confidence: 99%